Kazakhstan Economic Update, Summer 2016 : A Long Road to Recovery - World Bank Group (World Bank, Washington, DC, 2016)
This edition of the Kazakhstan Economic Update is part of a biannual series designed to monitor economic developments in Kazakhstan. It presents a concise analysis of macroeconomic and structural conditions from late 2015 through the first five months of 2016.